Recruiting and Encouraging Students to Complete Advanced Placement Science and Math Courses and Exams: Policies and Practices. (September 2019) - Judson, Eugene; Bowers, Nicole L.; Glassmeyer, Kristi
Although several studies have reported Advanced Placement (AP) growth, little attention has been paid to school- and classroom-level strategies that encourage students to enroll into AP courses and complete AP exams. This study focused on determining goals emphasized, and strategies used, by science and math teachers ( N = 143). Results indicated teachers believe the greatest value of AP is in providing college-type experiences and boosting subject confidence; they place less importance on goals of students earning passing scores and improving college admission chances. Comparison based on school socioeconomic status indicated Title I teachers view AP as having greater value and are significantly more likely to require students to complete AP exams than non-Title I teachers. Title I teachers used twice the amount of strategies to convince students to complete AP exams. Interestingly, more than one third of the teachers enticed students by waiving final exams in lieu of completing AP exams.